2015
DOI: 10.1002/ejp.692
|View full text |Cite
|
Sign up to set email alerts
|

Cervical 10 kHz spinal cord stimulation in the management of chronic, medically refractory migraine: A prospective, open‐label, exploratory study

Abstract: Paresthesia-free cervical HF10 SCS may be a safe and effective therapeutic option for chronic migraineurs refractory to conventional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 35 publications
5
49
0
1
Order By: Relevance
“…Our outcomes and safety data are consistent with data from both the HF10 treatment cohort from the initial European trial and also the randomized trial comparing HF10 to conventional spinal cord stimulation for chronic back and leg pain .…”
Section: Discussionsupporting
confidence: 81%
“…Our outcomes and safety data are consistent with data from both the HF10 treatment cohort from the initial European trial and also the randomized trial comparing HF10 to conventional spinal cord stimulation for chronic back and leg pain .…”
Section: Discussionsupporting
confidence: 81%
“…Another possible indication for 10 kHz SCS to date beyond trunk and/or limb pain is intractable headache (HA). A prospective, open‐label study by Arcioni and associates trialed the therapy in 17 subjects with refractory chronic migraine (CM) . Of these, 15 elected to have a permanent system, and 14 completed six months of follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective, openlabel study by Arcioni and associates trialed the therapy in 17 subjects with refractory chronic migraine (CM). 66 Of these, 15 elected to have a permanent system, and 14 completed six months of followup. All subjects had failed botulinum toxin therapy and were overusing medication at baseline.…”
Section: Intractable Headache (Off-label Indication For Scs)mentioning
confidence: 99%
“…A recent non‐industry‐sponsored clinical trial comparing conventional SCS and HF10 in 60 subjects with FBSS found that both groups had improved from baseline at 12 months; however, the pain reduction was less than previously reported, and there were no differences in pain or functional scores between the 2 groups . Additional retrospective studies in patients with headaches and primarily neuropathic pain have been encouraging, supporting the use of HF10 for segmental pain pathologies …”
Section: High‐frequency Stimulationmentioning
confidence: 86%